Culture and innovation: a study of Malay and Chinese women entrepreneurs in peninsular Malaysia - Aida Idris (2008)
Over the last two decades, considerable research interest has been shown on the effect of cultural values on innovation. Much of the research in this area is theoretically based upon psycho-sociological studies on the significance of cultural values as determinants of human behaviour. In general researchers have successfully established the connection between innovativeness and specific values such as fatalism, individualism and uncertainty avoidance (Tansuhaj et al, 1991; Shane, 1993; Mueller and Thomas, 2000; Thatcher et al, 2003). In most of these studies on culture-innovation relationships, two common characteristics have been observed: One, men are the majority respondents and two, there is no attempt to distinguish male and female responses to cultural stimuli. Sociologists have often described behavioural differences between men and women in certain value settings (Best and Williams, 1997; Hofstede, 1980). Masculine societies, in particular, expect men to be aggressive and women to be passive. They consistently emphasise male-female differences in social status and roles. As a result men and women choose different subjects at school and different careers, and they treat sons and daughters differently at home. Thus the social conditioning process induces gender differentiated behaviours in masculine societies. With this in mind, any research which combines men and women as a single cultural group is believed to be seriously misleading In Malaysia, issues of women's development as well as inter-ethnic relations and differences have always been central to nation-building. The heterogenous characteristic of the locals requires the government to have a deep understanding of the differences among the various ethnic groups. At the same time, since women comprise approximately half of the population (Department of Statistics, 2001), their social position also greatly affects the country's political and economic scenario. Certainly, in the area of management, scholars (Lang and Sieh, 1994; Fontaine and Richarson, 2003; Ong and Sieh, 2003) generally admit that more studies on women's participation and cross-cultural analysis are needed to help in the formulation of socio-economic policies and programmes. From the entrepreneurship point of view, the findings will have many implications on the management of businesses operating in a multi-cultural, gender-sensitive society. It is in the spirit of this multiculturalism and gender-sensitiveness that the idea for the current study is conceived. Focus is given on the Malay and Chinese ethnic groups because they comprise respectively around 60% and 30% of the Malaysian No need population (Department of Statistics, 2001). The decision to concentrate on women is based on the social conditioning theory which acknowledges women as a distinct cultural entity, while innovativeness is chosen to represent entrepreneurial behaviour due to its association with business performance (Kanter, 1984; Drucker, 1985; Heinecke, 2000; Johnson, 2001). The study employs a combination of qualitative and quantitative approaches. Personal interviews provide the preliminary information, particularly in areas not adequately represented in the existing literature. These include an appropriate measure for innovativeness among Malaysian women entrepreneurs. In the quantitative stage, path analysis is used to examine the direct and indirect relationships among three sets of variable: Ethnicity as the independent variable, entrepreneurial innovativeness as the dependent variable, and cultural values - in particular masculinity and uncertainty avoidance - as the mediating variables. The study concludes that for a female sample, masculinity should not be treated as a single-construct dimension as practised by Hofstede (1980) himself. Rather it should be split into two "sub"-consructs i.e. ego orientation and gender differentiation. Results indicate that the Malay sample is more innovative than the Chinese even though the latter has a higher index of ego orientation. This may be explained by the former's lower index of gender differentiation. Other significant findings of the study include the development of a more gender-sensitive scale of entrepreneurial innovativeness, as well as suggestions for additional mediating and moderating variables.